2015
DOI: 10.1038/ijos.2015.26
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of α-smooth muscle actin and tenascin-C in the periodontal ligament under orthodontic loading or in vitro culture

Abstract: α-smooth muscle actin (α-SMA) and tenascin-C are stress-induced phenotypic features of myofibroblasts. The expression levels of these two proteins closely correlate with the extracellular mechanical microenvironment. We investigated how the expression of α-SMA and tenascin-C was altered in the periodontal ligament (PDL) under orthodontic loading to indirectly reveal the intrinsic mechanical microenvironment in the PDL. In this study, we demonstrated the synergistic effects of transforming growth factor-β1 (TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
(57 reference statements)
1
20
0
Order By: Relevance
“…Considering that cell populations in PDL tissue contract and stretch repeatedly in a similar manner to vascular muscle cells because of their constant exposure to masticatory and occlusal pressure, PDL cells might share some characters with smooth muscle cells. Alternatively, PDL cells expressing transgelin strongly could possess the characteristics of myofibroblast as it has been reported that TGF‐β1 induced the differentiation of PDL cells into myofibroblasts under specific conditions . To clarify the characteristics of PDL cells expressing α‐SMA or transgelin in detail, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that cell populations in PDL tissue contract and stretch repeatedly in a similar manner to vascular muscle cells because of their constant exposure to masticatory and occlusal pressure, PDL cells might share some characters with smooth muscle cells. Alternatively, PDL cells expressing transgelin strongly could possess the characteristics of myofibroblast as it has been reported that TGF‐β1 induced the differentiation of PDL cells into myofibroblasts under specific conditions . To clarify the characteristics of PDL cells expressing α‐SMA or transgelin in detail, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, PDL cells expressing transgelin strongly could possess the characteristics of myofibroblast as it has been reported that TGF-β1 induced the differentiation of PDL cells into myofibroblasts under specific conditions. 33 To clarify the characteristics of PDL cells expressing α-SMA or transgelin in detail, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used were as previously described [30]. In brief, rats were anesthetized by an intraperitoneal injection of 10% chloral hydrate (3 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Complementary DNA (cDNA) was prepared by using a TaKaRa PrimerScript 1 st Strand cDNA Synthesis Kit (TaKaRa, Tokyo, Japan) andRT-qPCR was done as previously described [33]. Briefly, a total 20μL cDNA mixture was subjected to PCR amplification.…”
Section: Methodsmentioning
confidence: 99%
“… 14 α-SMA-positive cells are also present in the PDL during orthodontic tooth movement, indicating that enhanced mechanical stress promotes myofibroblast differentiation. 15 …”
Section: Introductionmentioning
confidence: 99%